Innovation networks in metropolitan regions - the case of the Vienna urban region - Alexander Kaufmann (European Regional Science Association (ERSA), 2005)
Metropolitan regions are important locations of innovation networks. They comprise a broad variety of high tech firms, producer services, research organizations, financial organizations, training institutions and other private and public organizations which are contributing to innovation. Such regions, however, are typically larger than the administrative entity of the core city. This applies also to the greater Vienna urban region, the most important concentration of innovation-related institutions in Austria. This paper analyses the potential role of the municipal authorities of Vienna in supporting and shaping the metropolitan innovation system. This is a complex task because many important elements of the innovation networks of local firms are located outside the city or the metropolitan region. And even those organizations which have their physical location in the city are sometimes controlled from abroad (e.g. foreign owned subsidiaries) or by other, in particular national, administrative levels (e.g. federal universities). Based on a survey of innovation networks in the Vienna urban region, basic structural features of these networks - types of partners, their location and the kind of relations between them - are presented. From these results, conclusions concerning the design of urban innovation policy - its potential scope and effectiveness, reasonable priorities and inevitable limits - are drawn.
Keywords: 330